Cover Picture: Self‐Assembling Aryl‐Naphthalendiimide Derivatives with a Nitroxide Radical (Asian J. Org. Chem. 2/2013). Issue 2 (8th February 2013) - Nakatsuji, Shin'ichi; Aoki, Kazunori; Kojoh, Ayumi; Akutsu, Hiroki; Yamada, Jun‐ichi; Karakawa, Makoto; Aso, Yoshio
<x xml:space="preserve">Abstract</x> Polyflurophenyl‐ as well as 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO)‐substituted naphthalenediimide (NDI) derivatives form single component charge‐transfer complexes by self‐assembly. In their Full Paper on page 164 ff., Shin'ichi Nakatsuji et al. report the structures and properties of aryl‐substituted NDI derivatives that contain TEMPO radicals. From a yellow solution of the pentaflurorophenyl derivative came black crystals with the aggregated structure shown in the picture. Moreover, better field‐effect transistor properties were demonstrated for the polyfluorophenyl derivatives relative to the phenyl or 4‐fluorophenyl derivatives.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>